Analisis Pengembangan Desa Wisata Ekonomi Kreatif Di Kabupaten Ogan Komering Ilir - Fadlina, Siti (Program Studi Pariwisata Program Sarjana, Fakultas Pariwisata, Universitas Udayana, 2023)
The development of a tourism village based on a combination of natural, cultural, and creative tourist attractions has made creative economic activities in Ogan Komering Ilir (OKI) Regency a major tourist attraction. The research aims to look at the process of developing a creative economy tourism village in OKI Regency by analyzing the selection of potential tourism village development sites, analyzing the assessment of the tourism village category, and analyzing the needs of tourism village development. The research method uses qualitative research in the form of primary data collection (observations, surveys, and interviews), and secondary data collection from various institutional and literary sources. The analytical method uses data analysis, scoring, and weighting techniques. Respondents in the study were 13 informants from district governments, village/kelurahan offices, community groups, business managers, business owners, craftsmen, and artists. The results of the analysis of the selection of locations for the development of tourism villages based on the creative economy are that there are 10 villages/kelurahan with high scores. The results of the assessment analysis for the creative economy tourism village category are on average in the productive and innovative village category, with a component rating level on a medium scale. So the priority is handling and improving the components with low and medium scale, namely the components of human resources, assistance and collaboration, institutions, infrastructure, digital technology, and finance. Keywords: development analysis, creative tourism village, creative economy village, Ogan Komering Ilir